De Novo Large Deletion Leading to Fragile X Syndrome - Jiraanont, Poonnada; Manor, Esther; Tabatadze, Nazi; Zafarullah, Marwa; Mendoza, Guadalupe; Melikishvili, Gia; Tassone, Flora (Frontiers in Genetics, 2022)
Fragile X syndrome (FXS) is the most frequent cause of X-linked inherited intellectual disabilities (ID) and the most frequent monogenic form of autism spectrum disorders. It is caused by an expansion of a CGG trinucleotide repeat located in the 5’UTR of the FMR1 gene resulting in the absence of the Fragile X mental retardation protein, FMRP. Other mechanisms such as deletions or point mutations of the FMR1 gene have been described and account for approximately 1% of individuals with FXS. Here we report a seven-year-old boy FXS case with a de novo deletion of approximately 1.1 Mb encompassing several genes, including the FMR1 and the ASFMR1 genes, and several miRNAs, whose lack of function, could result in the observed proband phenotypes. In addition, we also demonstrate that FMR4 completely overlaps with ASFMR1, and there are no sequencing differences between both transcripts (named as ASFMR1/FMR4 throughout the manuscript).